Psoriasis An Interdisciplinary Approach to - Chiriac, Anca (IntechOpen, 2017)
In 2014, psoriasis was recognized as a serious noncommunicable disease in the World Health Assembly Resolution WHA67.9, with a great negative impact on patients' quality of life. Psoriasis is a worldwide chronic disease, affecting all ages and all races, and a serious global health problem. Psoriasis is a complex disease with still unknown etiology and no specific curative treatment. The chapters provide comprehensive and new description of some issues related to psoriasis research and for understanding of clinical correlations, genetic aspects, experimental research, and potential therapeutic interventions. The book could be a source of information for clinicians and researchers from different fields in raising awareness of the disease.